Natural Products and Disease Prevention, Relief and Treatment - Islam, Md Soriful (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The consumption of fruits, vegetables, herbs, spices, etc., is thought to be associated with reduced risk for many human diseases, including cancers. Recently, significant advances have been made in evaluating the efficacy of natural products (compounds from natural sources) against human diseases. The purpose of this Special Issue, "Natural Products and Disease Prevention, Relief and Treatment", was to collect manuscripts concerning natural products for treating human diseases. Consequently, we have collected several high-quality manuscripts that focus on the molecular mechanisms of natural products, including their anti-inflammatory, antioxidative, neuroprotective, cardioprotective, antifibrotic, and anticancer effects, as well as other health beneficial effects across a wide range of human diseases. Overall, this Special Issue is an excellent source for information on promising natural products for future preclinical and clinical research into multiple diseases.